MicroRNA -140-5p inhibits colorectal cancer invasion and metastasis by targeting ADAMTS5 and IGFBP5. Issue 1 (December 2016) - Yu, Lihui; Lu, Ying; Han, Xiaocui; Zhao, Wenyue; Li, Jiazhi; Mao, Jun; Wang, Bo; Shen, Jie; Fan, Shujun; Wang, Lu; Wang, Mei; Li, Lianhong; et al.
Abstract Background Colorectal cancer (CRC) is one of the most common malignancies in the world. microRNA-140-5p (miR-140) has been shown to be involved in cartilage development and osteoarthritis (OA) pathogenesis. Some contradictions still exist concerning the role of miR-140 in tumor progression and metastasis, and the underlying mechanism is uncertain. Methods Immunohistochemistry was performed to determine the expressions of ADAMTS5 and IGFBP5 in CRC tissues. Human CRC cell lines HCT116 and RKO were transfected with miR-140 mimic, inhibitor, or small interfering RNA (siRNA) against ADAMTS5 or IGFBP5, respectively, using oligofectamine or lipofectamine 2000. Scratch-wound assay and transwell migration and invasion assays were used to evaluate the effects of miR-140 on the capabilities of migration and invasion. The levels of miR-140 and ADAMTS5 and IGFBP5 mRNA were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Western blot was performed to examine the expression of ADAMTS5 and IGFBP5 proteins. Results miR-140 was significantly reduced, whereas ADAMTS5 and IGFBP5 were upregulated, in the human CRC tissues compared to the corresponding normal colorectal mucosa. miR-140 downregulation and ADAMTS5 or IGFBP5 overexpression were associated with the advanced TNM stage and distant metastasis of CRC. There was a reverse correlation between miR-140 levels and ADAMTS5 and IGFBP5 expression in CRC tissues. ADAMTS5 and IGFBP5 were downregulated by miR-140 at both the protein and mRNA levels in the CRC cell lines. The gain-of- and loss-of-function studies showed that miR-140 inhibited CRC cell migratory and invasive capacities at least partially via downregulating the expression of ADAMTS5 and IGFBP5. Conclusions These findings suggest that miR-140 suppresses CRC progression and metastasis, possibly through downregulating ADAMTS5 and IGFBP5. miR-140 might be a potential therapeutic candidate for the treatment of CRC.